Perceptions of The Culinary Art Community On Their Higher Education Programs in Egypt: The Way Forward - Abdel Motaal, Kadria Ali (AUC Knowledge Fountain, 2023)
Culinary art education used to have a narrow focus that forgoes its richness and ignores its infiltration into economic, political, and cultural aspects within society. Recently the world witnessed an evolution in this field of study as it reached tertiary education institutions. However, in Egypt, culinary art studies are integrated into hospitality education and are still confined to a shallow concept. This study aimed to explore the perception of the culinary art community in Egypt on their higher education programs from a sociocultural perspective. It also explored the possible new frameworks, and core competencies to improve culinary arts higher education curricula in Egypt. The study used a qualitative research methodology based on a case study strategy for inquiry. Data were collected via focus group discussions, and individual interviews. Data analysis relied on a combination of deductive, and inductive approaches to classify the results under five main themes. The findings confirmed the literature review on many points like the social connotation of food, and the divided perception of the culinary arts’ higher education in Egypt between the traditional mindset that considers it a vocational field, and the emerging experts who see the potential of this field as an academic discipline based on scientific knowledge. Also, the gap in Egyptian higher education in culinary art was confirmed, the participants called for an education that promotes creativity, and innovation. The study proposed a multidisciplinary curriculum framework for culinary art higher education, to serve as guiding reference for the future development of this discipline.